Belowground plant biomass allocation in tundra ecosystems and its relationship with temperature - Wang, Peng; Heijmans, Monique M P D; Mommer, Liesje; van Ruijven, Jasper; Maximov, Trofim C; Berendse, Frank (Environmental research letters, 2016)
Climate warming is known to increase the aboveground productivity of tundra ecosystems. Recently, belowground biomass is receiving more attention, but the effects of climate warming on belowground productivity remain unclear. Enhanced understanding of the belowground component of the tundra is important in the context of climate warming, since most carbon is sequestered belowground in these ecosystems. In this study we synthesized published tundra belowground biomass data from 36 field studies spanning a mean annual temperature (MAT) gradient from −20 °C to 0 °C across the tundra biome, and determined the relationships between different plant biomass pools and MAT. Our results show that the plant community biomass-temperature relationships are significantly different between above and belowground. Aboveground biomass clearly increased with MAT, whereas total belowground biomass and fine root biomass did not show a significant increase over the broad MAT gradient. Our results suggest that biomass allocation of tundra vegetation shifts towards aboveground in warmer conditions, which could impact on the carbon cycling in tundra ecosystems through altered litter input and distribution in the soil, as well as possible changes in root turnover.